2015
DOI: 10.1186/s12913-015-0719-1
|View full text |Cite
|
Sign up to set email alerts
|

Use of GP services by patients with schizophrenia: a national cross-sectional register-based study

Abstract: BackgroundReform of health services has given primary care facilities increased responsibility for patients with serious mental disorders (SMD). There has also been a growing awareness of the high somatic morbidity among SMD patients, an obvious challenge for general practitioners (GPs). The aim of this study was to assess the utilisation of GP services by patients with schizophrenia.MethodsThe Norwegian list patient system is based on fee-for-service (FFS). For each contact, the GPs send a claim to National H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 33 publications
5
8
0
5
Order By: Relevance
“…The multilevel linear regression showed that women made more visits to their GP, which is in line with other studies [ 4 , 15 , 19 ]. The analysis also showed that patients who were married or living with a partner had more contact with PPCs than singles, as in an earlier study [ 15 ] and this may have been because family support helped to ensure they received continuing care.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The multilevel linear regression showed that women made more visits to their GP, which is in line with other studies [ 4 , 15 , 19 ]. The analysis also showed that patients who were married or living with a partner had more contact with PPCs than singles, as in an earlier study [ 15 ] and this may have been because family support helped to ensure they received continuing care.…”
Section: Discussionsupporting
confidence: 91%
“…The mean annual number of patient contacts with GP was 4.1, which is in line with other reports [ 5 , 16 , 19 ]. Our results show that in the area we studied the majority of patients were in contact with primary care professionals, only 3.2% had no contact with a GP during the observation period, which is even lower than in a study conducted in Norway, in which the percentage of patients who had no contacts with a GP was 17% [ 19 ].…”
Section: Discussionsupporting
confidence: 91%
“…Rates of access to general practice for schizophrenia were commensurate with population estimates of prevalence. This is consistent with studies demonstrating that most people diagnosed with schizophrenia have regular contact with a general practitioner [ 7 , 34 ], often for administration of antipsychotic medication and/or the management of physical health problems that commonly co-occur with psychotic illnesses [ 35 ]. Compared to those who access public mental health services, people with schizophrenia who access general practice experience fewer symptoms, improved functioning, and lower service use [ 36 ].…”
Section: Discussionsupporting
confidence: 87%
“…Regarding hospitalizations, the median LOS of hospitalizations encoded with a SD diagnosis associated (21095) was 4 days, whereas our average LOS was 10 days (data not shown). Although these results are comparable to other European studies [43][44][45], the average LOS of acute psychotic episodes may be longer [46]. The fact that we considered hospitalizations for SD in any diagnosis position could have influenced these estimates.…”
Section: Discussionsupporting
confidence: 82%